Perempuan, Alam, Siluman, dan Tabu dalam Novel Burak Siluman Karya Moh. Ambri: Tinjauan Realisme Magis - Asep Yusup Hudayat (Tsaqofah, 2021)
Women, nature, ghost, and taboo are the main discourses related to magical realism in “Burak Siluman”, a novel by Moh. Ambri. In Burak Siluman, women (the main sign) were connected to the discourse of nature, ghost, and taboo. In it, women represent the suppressed desires of the lower class for wealth, position, honor wrapped in narratives of fascination, search, wandering, misfortune, and a curse. Discourses on the supernatural, half-ghost, and taboo legends in the novel are important traditional realities that are studied and seen by the workings of the concepts of magical realism in the colonial period of the Dutch East Indies. The main problem is: how does the concept of magical realism affect the construction of the world (physical and supernatural), especially related to ghost and taboo narratives in “Burak Siluman”. Thus, the main objective of this research is the interaction of the influence of magical realism on narratives construction related to women, nature, ghost, and taboo. To resolve the issue, the concept of contemporary magical realism is used from a postcolonial perspective. The results of this study is the placement of the "between" space (magic in rational) which is represented in the wandering figure is the core idea of ​​magical realism in “Burak Siluman”.